Солнечная навигация птиц - Назарчук, Г.К.; Кистямовсхий, А.Б.; Смогоржевский, Л.А.; Шульман, Л.М. (Вестник зоологии, 1969)
The article deals with the birds orientation as to the Sun. The variant, which is the easiest for birds to orient themselves, is chosen out of the infinite number of possible variants. This is the method to determine the direction to home from the position angle of the solar motion and the Sun height above the horizon. Determining the above-mentioned parameters and comparing them in the place of setting free and at home for the same moment of time, a bird gets necessary data to choose the right direction.
On the basis of the experimentary data on homing oi Riparia riparia L., Hirundo rustica L., Delichon urbica L. and Sturmus vulgaris L., it was established that the optimal conditions for birds orientation are observed not near home but at a distance of 20—40 km from it.